CREATION OF NEW MATERIALS FOR MOLECULAR ELECTRONICS – ORGANIC LIGHT-EMITTING DIODES, FIELD TRANSISTORS, SOLAR CELLS AND ELECTROCHROMIC DEVICES - Shklyaeva, E.V.; Sosnin, E.A.; Ignatenko, E.A.; Romanova, V.A.; Osorgina, I.V.; Selivanova, D.G.; Abashev, G.G. (Perm Federal Research Centre Journal, 2014)
A large-scale set of new V-shaped conjugated monomers with an electron-deficient pyrimidine ring as a central core, conjugated with electron-donating fragments: 2-thienyl, 3-thienyl, pyrrol-1-yl, 2,5- di(2-thienyl)pyrrol-1-yl, carbazol-9-yl, carbazol-3(6)-yl, phenothiazin-2-yl, phenyl, etc., was prepared. Some new conjugated systems embedding different hydroquinolines into the conjugation chain were elaborated and synthesized. New -donors of tetrathiafulvalene class incorporating either only electron- donating chemically and electrochemically polymerizable fragments such as 2,5-di(2-thienyl)pyrrol-1- yl, or electron-donating and electron-deficient fragments simultaneously, for example such as 4,6-di(2- thienyl)-1,3,5-tirazine or 4,6-di(p-tolyl)-1,3,5-triazine, were prepared as well.The structures of some newly synthesized heterocycles were confirmed by X-Ray analysis. Electrochemical behaviour of all the prepared compounds was studied using cyclic voltammetry method. There were films of polymers on the surface of ITO (Pt) electrode obtained. Some of the synthesized substituted pyrimidines were chemically polymerized. Using data of optical spectra and data of cyclic voltammetry measurements we calculated HOMO and LUMO levels and the band gaps of the prepared polymer films. UV–vis absorption and fluorescence spectroscopy of all compounds was measured and studied.